Colicin cleavage by OmpT protease during both entry into and release from Escherichia coli cells. - Cavard, D (1990)
Proteolysis of colicins A, E1, E2, and E3 was observed after they were added to whole cells carrying a functional ompT gene. Recombinant plasmid pML19 containing the ompT gene enabled two mutant strains to cleave the added colicins. On the other hand, two colicin A recombinants were split after release from the wild-type bacteria that produced them but not from ompT mutant cells.